ANALISA KETINGGIAN AIR PADA TANGKI BLOWDOWN MENGGUNAKAN METODE ZIEGLER – NICHOLS DI PT MITRA ENERGI BATAM - Irsyam, Muhammad; Algusri, Missyamsu; Mubarok, Barep Sopan (SIGMA TEKNIKA, 2023)
The control system is the treatment that is carried out so that the system can run as it should. The aim of this control system is to achieve optimal, effective and efficient working conditions in a system. One example of a control system that is widely used today in industry is PID (Proportional, Integral and Derivative) control. Until now, some control system designers still have difficulty setting PID controller parameters. In this research, the author wants to know the differences between PID controllers using the Ziegler-Nichols tuning method. From the simulation results above using the Ziegler-Nichols method using the reaction curve method, the values Kp = 6.07, Ki = 1.37, and Kd = 6.67 were obtained with less than optimal signal response results where there was still an overshoot of 9.2% so that the Kp, Ki values were repeated. , and Kd using the second simulation method to obtain optimal signal response results with an overshoot of 0.49%, with values of Kp = 10.87, Ki = 1.42 and Kd = 6.83. And this research is to carry out a simulation to get a signal response using Matlab 2017b simulation on Simulink. Which can make it easier for us to create a PID controller block diagram.